The Arabic translation and commentary of Yefet ben 'Eli the Karaite on the Book of Joshua - Robinson, James T.; Japheth ben Ali, ha-Levi, active 10th century (Études sur le judaïsme médiéval ;, 2015)
Yefet ben 'Eli (fl. 960-1005) was the most prolific and influential biblical exegete in the Karaite tradition. However, only a small percentage of his commentaries have been published. The present volume makes available for the first time his commentary Joshua.